More Precious Than Rubies - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet is themed upon the importance of youth education and how critical it is for a child's study environment to be conducive to focus. Consists of dialogue between a character named Mrs. Marshall and the narrator. The narrator describes ways that Mrs. Marshall could redesign her children's study environment to help them perform better in school. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc., formed in 1933, was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Paint materials; Varnish and varnishing; Paint industry and trade; Advertising--Paint; Education; Study skills; Interior decoration